Complement analysis in the 21st century - Mollnes, Tom; Jokiranta, T. Sakari; Truedsson, Lennart; Nilsson, Bo; Rodriguez de Cordoba, Santiago; Kirschfink, Michael (Molecular immunology, 2007)
Complement analysis in the clinic is usually associated with the quantification of C3 and C4, measurement of C1-inhibitor and screening for complement activity. These analyses have been available in routine diagnostic laboratories for decades. In recent years, however, the field of complement analysis has expanded considerably, with the introduction of novel assays to detect complement activation products, and spreading still further towards genetic analysis to reveal the basis of complement deficiencies and identify mutations and polymorphisms associated with defined diseases such as atypical haemolytic uraemic syndrome and age related macular degeneration. Here we review the current status of complement analysis, including assays for the quantification of complement activity and complement activation products, together with genetic methods for the detection of deficiencies, mutations and polymorphisms. This is an area where significant developments have been made recently, paralleling the research advances into the role of complement in human disease. It is clear, however, that there is a need for consensus and standardisation of analytical methods. This will be a major challenge for the complement society in the future.
Gesehen am 18.06.2021